Effects of Capital Flight on Economic Growth in Selected ASEAN Economies - Siah, Kim Lan (2009)
Prior to the Asian financial crises, Indonesia, Malaysia, the Philippines and Thailand had experienced strong and impressive real economic growth rate from the 1970s to until beginning of 1997. Conventional wisdom hold that with the region’s impressive economic growth associated with higher interest returns and lower risk would expect capital to stay in the countries but not flee. However, it was quite surprising that even during periods of high economic growth rate; there was capital flight in these selected ASEAN economies. The lost of capital through capital flight will intensify capital scarcity problem as it restricts the capacity and the ability to finance domestic investment where resources are most needed to generate economic growth and development particularly after the Asian financial crisis of 1997. Although there are no universally accepted and indisputable definitions of capital flight, however, it is generally agreed that capital flight is the outflow of capital that is conflict with national interests, goals and objective. For the empirical work, the ARDL ‘Bounds test’ approach to cointegration was conducted with annual time series data from 1972 to 2005 to determine factors affecting capital flight from Indonesia, Malaysia, the Philippines and Thailand using World Bank measure, Morgan Guaranty Trust measure and Dooley Derived measure. By using the three alternative measures of capital flight, yields broadly similar results. On one hand, the results indicate that higher capital flight is associated with higher external debt, higher budget deficit as well as higher political instability that proxy by Political rights. On the other hand, the elasticities indicate that higher capital flight is associated with lower Interest rates differential (United States Treasury Bill rate minus domestic deposit rate), and lower accumulation of international reserve. However, the estimated results reveal that only higher capital flight is associated with higher Interest rates differential in Thailand case. Although there are large and growing researches for the determinants of economic growth, there has scarcely been any study concerning the impact of capital flight on economic growth. The empirical results support the contention that capital flight played a crucial role in influencing the four selected ASEAN economic growths. Furthermore, there has been no systematic investigation of the impact of political instability on capital flight and economic growth, particularly the ASEAN countries. The empirical results clearly show that political stability plays an important role in affecting capital flows and in determining economic growth in these four Southeast Asia economies. For a flight relief or even reversal of capital flight to occur as well as to stimulate economic growth, steps includes economic policies, political stability and institutional developments should be taken to prevent the causes of capital flight to ensure sufficient capital resources required for recovery from the current recession in the short-run and accomplish a more sustainable impressive economic growth in the long run. Indeed, the more preferred and effective strategy would be to implement balanced policy measures but not just bias on one or just certain aspects of macroeconomic fundamentals, perhaps, the adaptation of appropriate policy to suit varying circumstances of the economy is more important. Any policy announcements by the government should be in line with the long-term objectives of the country.